Anti-PS IgG Immune Complexes Impair Macrophage Phagocytosis in SLE via LOX-Dependent Oxidative Stress - Guan H; Huang L; Liu Y; Zhu E; Chen L; Li W; Wu H; Zhang X; Qin R; Zheng J; Mo Y; Zhong M; et al. (Journal of Inflammation Research)
Hui Guan,1– 3,* Liqi Huang,1,* Yu Liu,1,* Enyi Zhu,4 Lefeng Chen,5 Weijie Li,2 Haiqi Wu,2 Xiaoying Zhang,6 Rencai Qin,2 Jingpeng Zheng,2 Yingqian Mo,5 Ming Zhong,1 Bihua Xu,7 Xiaoyan Dai,8 Qi Wei,2 Yunwei Chen,2 Qingwen Wang,7 Zhihua Zheng,1 Kongyang Ma,2 Chun Tang1 1Department of Nephrology, Center of Kidney and Urology, the Seventh Affiliated Hospital, Sun Yat-Sen University, Shenzhen, 518107, People’s Republic of China; 2Centre for Infection and Immunity Studies, School of Medicine, The Sun Yat-sen University, Shenzhen, 518107, People’s Republic of China; 3Department of Radiation Oncology, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, 450052, People’s Republic of China; 4The Division of Nephrology, The Sixth Affiliated Hospital, Sun Yat-Sen University, Guangdong Provincial Key Laboratory of Colorectal and Pelvic Floor Diseases, Guangzhou, 510000, People’s Republic of China; 5Department of Rheumatology, Sun Yat-sen Memorial Hospital of Sun Yat-Sen University, Guangzhou, 510120, People’s Republic of China; 6Health Management Center, the Seventh Affiliated Hospital, Sun Yat-Sen University, Shenzhen, 518107, People’s Republic of China; 7Department of Rheumatology and Immunology, Peking University Shenzhen Hospital, Shenzhen, 518036, People’s Republic of China; 8Clinical Research Institute, Hengyang Medical School, the second Affiliated Hospital, University of South China, Hengyang, 421002, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chun Tang, Email tangch28@mail.sysu.edu.cn Kongyang Ma, Email makyang@mail.sysu.edu.cnPurpose: Systemic lupus erythematosus (SLE) is a severe autoimmune disease with systemic complications mediated by immune-complex formation. The elevated level of anti-phosphatidylserine (PS) IgG has been implicated in SLE pathogenesis. In this study, we aimed to explore the effector mechanisms of PS immune-complex during lupus development.Patients and Methods: Serological profiles of immune-complexes in SLE patients were analyzed. Immunofluorescence staining showed PS-IgG immune-complex deposition in kidney biopsies of lupus nephritis patients. C57BL/6J mice were immunized with PS for immune-complex and renal function assessment. The roles of PS-IgG immune-complex and lysyl oxidase (LOX) were validated from SLE PBMCs, THP-1 cell line and PS-immunized lupus mice. The intracellular reactive oxygen species (ROS) levels, and phagocytosis function were examined by flow cytometry in SLE PBMCs, THP-1 cell line and PS-immunized lupus mice. For in vitro treatment, the effects of antioxidant N-acetylcysteine (NAC) and LOX inhibitor β-Aminopropionitrile (BAPN) were verified in THP-1 cell line and cells from PS-immunized lupus mice.Results: SLE and lupus nephritis (LN) patients showed significant elevated circulating and glomerular PS-IgG immune-complex levels. ROC analysis indicated PS-IgG immune-complex as a strong biomarker in SLE and LN. Mechanistically, induced macrophages from SLE patients treated with PS-IgG immune-complex significantly increased cytoplasmic ROS levels, elevated LOX expression and exhibited dampened phagocytotic function. In mice, PS immunization triggered PS-IgG immune complex formation, increased LOX expression, immune-complex deposited glomerular nephritis, and impaired phagocytotic function of macrophages. NAC and BAPN treatment restored the phagocytotic function of human and murine macrophages.Conclusion: Our results indicate that PS-IgG immune-complex can directly impair macrophage phagocytotic functions via LOX mediated-oxidative stress and may serve as a novel biomarker for SLE.Keywords: systemic lupus erythematosus, anti-phospholipid antibodies, immune complex, macrophages